Perawatan Periodontal pada Kehamilan - Nursolihati, Vidya (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Periodontal disease is a global health problem that affects up to 90% of the population and can worsen during pregnancy due to hormonal changes. This condition increases the risk of Adverse Pregnancy Outcomes (APOs), such as preeclampsia, premature labor, and low birth weight. Proper periodontal care during pregnancy is essential to prevent these complications. Objectives: Identifying effective and safe periodontal treatments for pregnant women to reduce the risk of periodontal disease and related pregnancy complications. Methods: The research was conducted by reviewing literature regarding the relationship between periodontal disease and pregnancy, pathophysiological mechanisms, as well as treatment approaches. Results: Non-surgical periodontal therapy has been proven to reduce gingival inflammation and improve the periodontal health of pregnant women. Treatment in the second trimester has been found to be safest for elective procedures, while certain medications, such as amoxicillin and chlorhexidine, can be used safely. Conclusion: Periodontal treatment during pregnancy is effective in improving periodontal health and reducing the risk of APOs. This therapy is highly recommended for use during pregnancy to support better pregnancy outcomes.